METODE EVALUSI ILLUMINATIVE DALAM UPAYA MENGATASI PERBEDAAN KEMAMPUAN SISWA DALAM MENGIKUTI PEMBELAJARAN BAHASA ARAB TINGKAT SEKOLAH MENEGAH ATAS - Fahmi Syaefudin; Umi Baroroh (STAI Masjid Syuhada Yogyakarta, 2023)
In the learning process, teachers need a result of the learning activities carried out so that they can determine and prepare the right strategies for the next learning activity. Learning outcomes are usually produced from the process of evaluating the results and learning processes of students that are already running. This research uses descriptive qualitative research methods by taking data from the literature and finding problems in the field. The results of this study discuss heterogeneous classes and how to use illuminative evaluation methods in arabic language learning in that class. The conclusion is that this method can be an alternative in evaluating learning with classroom conditions that have a variety of student backgrounds.